Cannabidivarin completely rescues cognitive deficits and delays neurological and motor defects in male Mecp2 mutant mice. (July 2019) - Zamberletti, Erica; Gabaglio, Marina; Piscitelli, Fabiana; Brodie, James S; Woolley-Roberts, Marie; Barbiero, Isabella; Tramarin, Marco; Binelli, Giorgio; Landsberger, Nicoletta; Kilstrup-Nielsen, Charlotte; Rubino, Tiziana; Di Marzo, Vincenzo; et al.
Background: Recent evidence suggests that 2-week treatment with the non-psychotomimetic cannabinoid cannabidivarin (CBDV) could be beneficial towards neurological and social deficits in early symptomatic Mecp2 mutant mice, a model of Rett syndrome (RTT). Aim: The aim of this study was to provide further insights into the efficacy of CBDV in Mecp2 -null mice using a lifelong treatment schedule (from 4 to 9 weeks of age) to evaluate its effect on recognition memory and neurological defects in both early and advanced stages of the phenotype progression. Methods: CBDV 0.2, 2, 20 and 200 mg/kg/day was administered to Mecp2 -null mice from 4 to 9 weeks of age. Cognitive and neurological defects were monitored during the whole treatment schedule. Biochemical analyses were carried out in brain lysates from 9-week-old wild-type and knockout mice to evaluate brain-derived neurotrophic factor (BDNF) and insulin-like growth factor-1 (IGF-1) levels as well as components of the endocannabinoid system. Results: CBDV rescues recognition memory deficits in Mecp2 mutant mice and delays the appearance of neurological defects. At the biochemical level, it normalizes BDNF/IGF1 levels and the defective PI3K/AKT/mTOR pathway in Mecp2 mutant mice at an advanced stage of the disease. Mecp2 deletion upregulates CB1 and CB2 receptor levels in the brain and these changes are restored after CBDV treatment. Conclusions: CBDV administration exerts an enduring rescue of memory deficits in Mecp2 mutant mice, an effect that is associated with the normalization of BDNF, IGF-1 and rpS6 phosphorylation levels as well as CB1 and CB2 receptor expression. CBDV delays neurological defects but this effect is only transient.